2020
DOI: 10.1002/bab.1935
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, characterization, and enzymatic identification of a new tryptophan decarboxylase from Ophiorrhiza pumila

Abstract: Tryptophan decarboxylase (TDC, EC 4.1.1.28) catalyzes tryptophan decarboxylation to form tryptamine through the cofactor pyridoxal‐5′‐phosphate (PLP), a crucial stage in the production of the terpenoid indole alkaloids like camptothecin (CPT). A new gene encoding TDC was identified from the CPT‐producing plant Ophiorrhiza pumila by transcriptome analysis, termed OpTDC2. It contained a 1,536 bp open reading frame that encodes a 511 amino acid protein with a molecular mass of 57.01 kDa and an isoelectric point o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…L-tryptophan decarboxylase (TDC) is a cytosolic type-II aromatic l -amino acid decarboxylase [ [53] , [54] , [55] , [56] , [57] ]. It catalyzes the final step in the microbial pathway of serotonin synthesis.…”
Section: Synthesis and Modification Pathways Of Melatonin In Microorganismsmentioning
confidence: 99%
“…L-tryptophan decarboxylase (TDC) is a cytosolic type-II aromatic l -amino acid decarboxylase [ [53] , [54] , [55] , [56] , [57] ]. It catalyzes the final step in the microbial pathway of serotonin synthesis.…”
Section: Synthesis and Modification Pathways Of Melatonin In Microorganismsmentioning
confidence: 99%
“…O. pumila has been considered to be a valuable alternative source of camptothecin (CPT), which is widely used to treat various cancers, such as colorectal, ovarian and lung cancer [ 9 , 10 ]. Studies refer to the biosynthesis process of CPT in O. pumila are decumulating [ 8 , 11 , 12 ], but the function of O. pumila compounds in cancer have rarely been explored. Previously, we reported that treatment with O. pumila extract (OPE) suppresses the proliferation and migration of liver cancer cells, indicating an anti-cancer activity of OPE in hepatocarcinoma [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic amino acid decarboxylases (AAADs) play important roles in the key step of 5-HTP conversion to 5-HT. Previously, tryptophan decarboxylase (TDC) was regarded as an enzyme that catalyses non-speci c reactions in L-trp or 5-HTP (prefer to L-trp), with the result that a one-pot cascade reaction cannot be performed and has therefore never been reported [10,11]. Dopa decarboxylase (DDC), another AAAD, is able to convert L-dopa to dopamine [12].…”
Section: Introductionmentioning
confidence: 99%